In-Hospital Depressed Level of Consciousness and Long-Term Functional Outcomes in ICU Survivors*. Issue 11 (23rd August 2022) - Mart, Matthew F.; Thompson, Jennifer L.; Ely, E. Wesley; Pandharipande, Pratik P.; Patel, Mayur B.; Wilson, Jo Ellen; Williams Roberson, Shawniqua; Birdrow, Caroline I.; Raman, Rameela; Brummel, Nathan E.
Abstract : OBJECTIVES: Among critically ill patients, acutely depressed level of consciousness is associated with mortality, but its relationship to long-term outcomes such as disability and physical function is unknown. We investigated the relationship of level of consciousness during hospitalization with long-term disability and physical function in ICU survivors. DESIGN: Multi-center observational cohort study. SETTING: Medical or surgical ICUs at five U.S. centers. PATIENTS: Adult survivors of respiratory failure or shock. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Depressed level of consciousness during hospitalization was defined using the Richmond Agitation Sedation Scale (RASS) score (including all negative scores) by calculating the area under the curve using linear interpolation. Sedative-associated level of consciousness was similarly defined for all hospital days that sedation was received. We measured disability in basic activities of daily living (BADLs), instrumental activities of daily living (IADLs), discharge destination, and self-reported physical function. In separate models, we evaluated associations between these measures of level of consciousness and outcomes using multivariable regression, adjusted for age, sex, race, body mass index, education level, comorbidities, baseline frailty, baseline IADLs and BADLs, hospital type (civilian vs veteran), modified mean daily Sequential Organ Failure Assessment score, duration of severe sepsis, duration of mechanical ventilation, and hospital length of stay. Of the 1, 040 patients enrolled in the ICU, 781 survived to hospital discharge. We assessed outcomes in 624 patients at 3 months and 527 patients at 12 months. After adjusting for covariates, there was no association between depressed level of consciousness (total or sedation-associated) with BADLs or IADLs at either 3- or 12-month follow-up. There was also no association with self-reported physical function at 3 or 12 months or with discharge destination. CONCLUSIONS: Depressed level of consciousness, as defined by the RASS, was not associated with disability or self-reported physical function. Future studies should investigate additional modifiable in-hospital risk factors for disability and poor physical function following critical illness.